CULTURAL AND SPIRITUAL BASIS OF SOCIAL INTEGRATION (International Congress on Economics, Management and Business Studies, 2026)
This article analyzes the cultural and spiritual foundations of social integration from a philosophical perspective. It highlights the spiritual and moral responsibility that the integration process places on man in the context of globalization, and substantiates the significance of the ideas of universal solidarity. It is shown that social integration is not limited to socio-economic relations, but is formed through culture, values, customs, religious and spiritual traditions. Based on the concepts of the philosophy of culture and spirituality, it is revealed that an individual's self-awareness, acceptance of others, and active participation in the system of common spiritual values is an important condition of social integration.
Keywords: social integration, philosophy of culture, spirituality, global integration, moral responsibility, social solidarity, value system, cultural harmony, individual and society, globalization.